Analisis Evaluasi Technology Acceptance Model terhadap Faktor-Faktor yang Mempengaruhi Penerimaan E-Procurement di Pemerintahan Provinsi Jawa Barat - Sarah Hana Fitriyah; Dewi Sri Wahyuni; Aan Julia; Nidar Nadrotan Naim (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Government functions require logistics, equipment and services to support optimal government activities by utilizing technology for administrative reform and public services that are transparent and accountable through e-Procurement. However, it turns out that the unpreparedness of human resources in operating e-Procurement affects its effectiveness. This research method is quantitative and descriptive using the Technology Acceptance Model (TAM). The population in this study is the Regional Apparatus/Bureau in West Java, the sample taken is 100 respondents from the Regional Apparatus/Bureau in West Java. The analysis tool uses Partial Least Square SEM using SmartPLS 3.0 software. Based on the results of the study, it is known that human resources who use e-Procurement in the West Java Provincial Government in its application have accepted the presence of e-Procurement even though in its application there are still users who experience difficulties. Keywords: e-Procurement, Public Service, Structural Equation Model, Technology Acceptance Model